Relationship Analysis Between Financial Literacy and Financial Distress (Among Young Adult Medan City) - Mayang Larasati; Andrieta Shintia Dewi (Universitas muhammadiyah malang, 2021)
Lack of skills in financial management and low knowledge of finances in young adults can cause errors in financial decision making and cause financial stress, which can be a challenge in the development of Medan City. This study aims to determine the relationship between financial literacy and financial distress in young adults in Medan City using quantitative methods by distributing questionnaires to 400 respondents. The results showed that the level of financial literacy in young adults in Medan City was high and the level of financial distress among young adults in Medan was moderate. Also, there is a strong positive relationship between financial literacy and financial distress in young adults in Medan City. This means that although young adults in Medan City are quite capable of making effective financial assessments and decisions, young adults in Medan City can be in a state of financial distress even though it is not significant. Keywords: Financial Literacy, Financial Distress, Medan City.